Bimaxillary Protrusion: An Overview of the Surgical-Orthodontic Treatment - Chu, Yong-Ming (Thieme Medical Publishers, 2009)
Bimaxillary protrusion is a commonly seen deformity in Asian populations. This condition is characterized by protrusive and proclined upper and lower incisors and an increased procumbency of the lips. It is usually combined with lip incompetence, gummy smile, mentalis strain, and anterior open bite. Facial aesthetics is the primary concern of these patients. Successful treatment depends on a thorough evaluation and understanding of this dentofacial deformity. Typical orthodontic treatment includes retraction and retroclination of maxillary and mandibular incisors after extraction of the four first premolars. Orthognathic surgery is required to correct significant skeletal problems. Anterior subapical osteotomies and extraction of premolars can correct sagittal excess of the jaw bones and relieve dental crowding. Segmental maxillary osteotomies are performed to treat patients with an associated exaggerated curve of Spee and vertical maxillary excess. Differential intrusion of anterior and posterior maxilla/maxillary segments with clockwise rotation of the occlusal plane is a useful technique for treatment of anterior open bite and creation of a consonant smile arc. Le Fort I osteotomy with setback sometimes provides an alternative to segmental maxillary osteotomies. Meticulous planning and execution of osteotomies in accordance with surgical planning are essential for aesthetic and functional outcome.